Azimuthal anisotropy beneath the deep central Aleutian subduction zone from normal mode coupling. (January 2020) - Cheng, Wei; Hu, Xiao-Gang; Liu, Lin-Tao
Highlights: We observe strong coupling of S 0 11 ??? T 0 12 due to local azimuthal anisotropy in Aleutian subduction zone. The fast direction in the depth of 400-700 km is trench parallel measured by normal mode coupling. The normal mode coupling can constrain the fast direction for the deep mantle. Abstract: Shear wave splitting measurements show that the anisotropy beneath central Aleutian subduction region is complex. Here we observed strong mixed coupling of S 11 0 - T 12 0 in the vertical component records at ADK station, a station deployed on the central Aleutians subduction zone, after the 2006/04/20 Olyutorsky earthquake, 2013/09/24 Pakistan earthquake and 2017/07/17 Nikol'skoye earthquake. We exclude the factor of Coriolis coupling and verify that the local azimuthal anisotropy is responsible for the strong coupling pair of S 11 0 - T 12 0 . We also estimate the coupling kernels depth and find the peak sensitivity for the coupled S 11 0 - T 12 0 is about 400-700km, which suggest the mantle transition zone(MTZ) beneath the central Aleutians has azimuthal anisotropy. Studies show that the strength of mixed coupling caused by local anisotropy depends on the azimuth of the source-receiver great circle. We compare our result with the fast orientation measured by wave splitting and find the fast direction of trench-parallel appears to be robust for central Aleutian at the 400-700km depth. The local azimuthal anisotropy plays a leading role on the coupled S 11 0 - T 12 0 in the early part records, however, the effects of local anisotropy on long period normal modes coupling are often ignored. Our observations indicate that the local anisotropy can make a noticeable effect on normal modes coupling. Normal modes coupling due to local anisotropy have high depth resolution, which can constrain the depth range of the azimuthal anisotropy mantle. The normal modes coupling signal can be a supplement to shear wave splitting technique in studying the anisotropy of subduction zone.